2018
DOI: 10.1515/dx-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy in Family Medicine residents using a clinical decision support system (DXplain): a randomized-controlled trial

Abstract: Family Medicine residents have appropriate diagnostic accuracy that can improve with the use of DXplain. This could help decrease diagnostic errors, improve patient safety and the quality of medical practice. The use of clinical decision support systems could be useful in educational interventions and medical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 29 publications
0
32
0
1
Order By: Relevance
“…While software cannot replace MDD, it can increase application of IPF guidelines in the community and allow referral of the most complex cases to regional centers for MDD. Many software platforms have been proposed to facilitate clinical decision making, demonstrating successful reducing costs and improving patient outcomes [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While software cannot replace MDD, it can increase application of IPF guidelines in the community and allow referral of the most complex cases to regional centers for MDD. Many software platforms have been proposed to facilitate clinical decision making, demonstrating successful reducing costs and improving patient outcomes [3].…”
Section: Discussionmentioning
confidence: 99%
“…Many software platforms has been proposed to facilitate clinical decision making demonstrateing successful in boosting physicians' diagnostic confidence, reducing costs and improving patient outcomes https://doi.org/10.1016/j.rmed.2018.12.011 Received 16 August 2018; Received in revised form 24 December 2018; Accepted 26 December 2018 [3].…”
Section: Introductionmentioning
confidence: 99%
“…DXplain is an electronic reference based DDSS that provides probable diagnosis based on clinical manifestations. 50 In a randomized control trial involving 87 family medicine residents, those randomized to use the system showed significantly higher accuracy (84% vs. 74%) on a validated diagnosis test involving 30 clinical cases. 50 Given the known incidence of diagnostic errors, particularly in primary care, 51 there is a lot of hope for CDSS and IT solutions to bring improvements to diagnosis.…”
Section: Clinical Managementmentioning
confidence: 97%
“…50 In a randomized control trial involving 87 family medicine residents, those randomized to use the system showed significantly higher accuracy (84% vs. 74%) on a validated diagnosis test involving 30 clinical cases. 50 Given the known incidence of diagnostic errors, particularly in primary care, 51 there is a lot of hope for CDSS and IT solutions to bring improvements to diagnosis. 52 We are now seeing diagnostic systems being developed with non-knowledge-based techniques like machine learning, which may pave the way for more accurate diagnosis.…”
Section: Clinical Managementmentioning
confidence: 97%
“…ontology with high transparency but the performance is often not as high (Cestnik et al, 1987;Miller, 2016;Martinez-Franco et al, 2018). Due to the high stake consequences of making medical diagnostic decisions it is important that the proposed DST solutions meet all proposed guidelines.…”
Section: Decision Support Tools' Requirements For Intelligent Roboticsmentioning
confidence: 99%